DIGITALISASI SISTEM LAPORAN DAN KINERJA KEUANGAN BERBASIS PROGRAM EXCEL BAGI USAHA MAHASISWA UNIVERSITAS JAMBI - Agus Syarif; Ahmad Nur Budi Utama; Erwita Dewi; Aulia Beatrice Brilliant; Istiqomah Malinda S.B (Bestari: Jurnal Pengabdian Kepada Masyarakat, 2025)
Community Service aims to enhance students' abilities in utilizing financial reports digitally, preparing reports, and managing financial performance using Excel. Financial reports are essential tools for assessing businesses’ condition and financial performance, including those run by students. Unfortunately, financial reporting is often overlooked, leading to conflicts within business teams. The fundamental reasons why student entrepreneurs fail to create financial reports include a limited understanding of bookkeeping, time constraints, and a lack of discipline. The community service methods include lectures, training, mentoring, and practical exercises. The results of the activities indicate an improvement in student entrepreneurs' ability to use financial reports digitally and manage financial performance based on Excel, as well as an increase in enthusiasm among student entrepreneurs to apply these skills in their businesses. Keywords: student entrepreneurship, financial reports, performance, digitalization